Resveratrol for inflammatory bowel disease in preclinical studies: a systematic review and meta-analysis - Gu, Yuting; Lou, Yijie; Zhou, Zhanyi; Zhao, Xuan; Ye, Xiaolu; Wu, Shuwen; Li, Haitao; Ji, Yunxi (Frontiers in Pharmacology, 2024)
Background: Inflammatory bowel disease(IBD)is a chronic condition that can be managed with treatment,but it is challenging to get IBD cured.Resveratrol, a non-flavonoid polyphenolic organic compound derived from various plants, has a potential effect on IBD.The current research was set out to investigate the therapeutic effects of resveratrol on animal models of IBD. Methods:A comprehensive search of PubMed,Embase,Web of Science,and Chinese databases was performed.The literature search process was completed independently by two people and reviewed by a third person.The risk of bias in the included literature was assessed using the Collaborative Approach to Meta Analysis and Review of Animal Data from Experimental Stroke(CAMARADES)10-point quality checklist.The meta-analysis utilized Review Manager 5.4 software to evaluate the efficacy of resveratrol, with histopathological index as the primary outcome measure.Subgroup analysis was conducted based on this indicator.Additionally,meta-analyses were carried out on different outcomes reported in the literature,including final disease activity index,final body weight change,colon length, splenic index, and inflammatory factors. Results:After conducting a thorough literature search and selection process,a total of 28 studies were ultimately included in the analysis.It was found that over half of the selected studies had more than five items with low risk of bias in the bias risk assessment.Relevant datas from included literatures indicated that the histopathological index of the resveratrol group was significantly lower than that of the control group(WMD=-2.58[-3.29, -1.87]).Subgroup analysis revealed that higher doses of resveratrol (> 80mg/kg) had a better efficacy(WMD=-3.47[-4.97,-1.98]).Furthermore,The data summary and quantitative analysis results of SI and colon length also showed that resveratrol was effective in alleviating intestinal mucosal pathological injury of IBD. In terms of biochemical indicators, the summary analysis revealed that resveratrol affected interleukin-1β(IL-1β),interleukin-6(IL-6),interleukin-8 (IL-8),interleukin-10(IL-10),tumor necrosis factor-α (TNF-α), transforming growth factor-β(TGF-β),interferon-γ(IFN-γ),malondialdehyde(MDA),myeloperoxidase(MPO),superoxide dismutase(SOD),and prostaglandin E2(PGE2)significantly.These effects may be attributed to the mechanism of resveratrol in regulating immune response and inhibiting oxidative stress. Conclusion:This review suggests that resveratrol demonstrated a notable therapeutic impact in preclinical models of IBD,particularly at doses exceeding 80mg/kg.This efficacy is attributed to the protective mechanisms targeting the intestinal mucosa involved in the pathogenesis of IBD through various pathways. As a result,resveratrol holds promising prospects for potential clinical use in the future.